PENGOLAHAN LIMBAH PLASTIK LDPE DAN PP UNTUK BAHAN BAKAR DENGAN CARA PIROLISIS - Arif Setyo Nugroho (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2020)
This study aims to determine the results of processing LDPE and PP plastic waste by means of pyrolysis, variations in temperatur of the pyrolysis reactor 300oC, 350oC, 400oC. The results of this study are expected to provide answers regarding the results of the pyrolysis of LDPE and PP waste pastes. The pyrolysis reactor is made of stenlis in the form of a tube with a diameter of 40 cm and a total height of 60 cm. Multilevel cooling, gas cooling using water passed in the pipe. The flow of water as a coolant with pyrolysis gas is in the opposite direction, the hope is that more oil is produced because the wasted gas is reduced. Heat energy comes from a burner made from LPG. The results of processing PP and LDPE plastic waste produce oil, solids (charcoal) and gas produced at each temperatur variation. A temperatur of 300oC produces less oil than a temperatur of 400oC in each type of PP and LDPE plastic. The higher the temperatur of the pyrolysis reactor, the more oil and cloudy it gets. All pyrolysis oil has a strong odor and when burned will produce soot.